Sebuah Menjelajahi Makna Denotatif dan Konotatif dalam Album 'The Search' oleh NF - Mochammad Iqbal Romadhon; Deny Kuswahono; Ari Astutik (EL2J (English Language and Literature Journal), 2024)
This research delves into the denotative and connotative meanings embedded in NF's album "The Search," employing Geoffrey Leech's theoretical framework to unveil the intricacies of the artist's song writing. Through qualitative analysis, the study explores multiple tracks from the album, categorizing the nuanced denotative and connotative layers within each song. Addressing themes such as fame, self-identity, mental health, and personal growth, NF's lyrics provide an introspective lens for listeners. The findings illuminate those 54 lyrics in the album encompass both denotative and connotative meanings, demonstrating NF's adept use of poetic language to convey narratives of wisdom, empowerment, and acknowledgment of life's challenges. The synthesis of denotative and connotative elements crafts a profound and evocative experience, fostering a connection between the artist and the audience. The research advocates for further exploration of NF's song writing process, encouraging comparative analysis with other artists in the genre to underscore his distinctive contributions to contemporary music. Overall, the study underscores the significance of uncovering deeper meanings in song lyrics, positioning NF's music as a platform for introspection, empathy, and meaningful connection. The application of Geoffrey Leech's theory enriches the comprehension of NF's artistic expression and its resonating impact on the audience.